Pharmacotherapy of drug resistance epilepsy: A Meta-analysis - Kamel, Fatemah (Journal of King Abdulaziz University: Medical Sciences, 2023)
Background: Epilepsy is a common neurological disorder. The primary objective of treatment with anti-elileptic drugs is to achieve seizure freedom. Objective: This systematic review and meta-analysis aimed to summarize the evidence-based medicine to treat drug-resistant focal epilepsy. Method: The literature search was done through electronic databases including PubMed, MEDLINE, Cochrane, Scopus, and Google Scholar for 1st January 2019 to 30 December 2022. The characteristics of selected drug-resistant focal epilepsy patients including the type of study, intervention, and treatment outcome were reported to estimate the reduction in seizure frequency. Study quality assessment was done using MMAT 2018. Results: A total of nine articles were included in this study for qualitative assessment. Five articles were included in the meta-analysis. A total of 6665 participants from all included studies were examined for the presence of drug-resistant focal epilepsy. The age of the study participants ranged from 1 month to 70 years. The included observational studies were on newer anti-elileptic drugs including lacosamide, levetiracetam, lamotrigine, and perampanel. The randomized control trials examined were on oral cannabidiol 25mg/kg/day or 50mg/kg/day dose versus placebo, 200 mg/d dose of cenobamate in patients with ≤ 3 anti-epileptic drugs, and oral cenobamate adjuvant dose of 100mg, 200mg and 400mg daily. The total 95% confidence interval for pooled seizure reduction frequency was 4.19 and I2 statistics 90.36 demonstrating marked heterogeneity between studies. Conclusion: To conclude, the use of third-generation and newer anti-seizure drugs has the potential to treat drug-resistant focal epilepsy.